Experimental investigation of desorption kinetics of methane in diesel and internal olefin for enhanced well control. Issue 2 (20th March 2020) - Ojedeji, Damilola; Perry, Scott; Nielsen, James; Chen, Yuanhang
Abstract: Early kick detection and well control decision‐making are more challenging when drilling with nonaqueous drilling fluids, largely due to the poor understanding of mass transfer kinetics of formation gas in and out of nonaqueous drilling fluids during these events. In this study, a laboratory‐scale experimental apparatus was developed and used to experimentally investigate the desorption kinetics of methane in diesel and internal olefin, which are among the most commonly used base fluids for oil‐based muds and synthetic‐based muds, respectively. Continuous measurements of discharge flow rates and totalized discharge volumes yield extent of desorption over time during each test. A model with a lumped mass transfer coefficient K L a was adopted for describing the desorption process in this study. Experimental methodologies with and without blanket gas were compared and the one without blanket gas was adopted due to its enhanced accuracy and repeatability. Time‐marching analysis was conducted to evaluate the instantaneous desorption coefficient during the entire bubble desorption process, while the maximum instantaneous desorption coefficient was used to characterize each desorption process. The effects of initial saturation pressure and base oil type on the resulting desorption coefficients were studied. According to the experimental results, the maximum instantaneous desorption coefficient is larger in diesel compared to the ones in internal olefins with the same initial saturation pressures. In addition, the maximum instantaneous desorption coefficient increases with initial saturation pressure for both fluids within the range of pressures that were considered in this study. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.